Modelling growth of Ruppia cirrhosa - Calado, Gonçalo (2007)
The main objectives of this work were to synthesise information on the autoecology of Ruppia cirrhosa Petagna (Grande) in a mathematical model and to use the model to simulate its growth, production and harvest. Model parameters were allowed to vary as a result of acclimation, following experimental data reported in the literature. Biomass data from Santo André lagoon (SW Portugal) were used to calibrate the model. Validation was carried out with independent data sets from Santo André lagoon and from Tancada lagoon (NE Spain). Model simulations show a reasonable agreement with observed data with a similar biomass temporal dynamics and peaks. Self-shading appears to be an important self-regulating mechanism of biomass growth and production. The results obtained predict an annual net primary production of 361 gDWm−2well within the estimates based on harvesting techniques (295–589 gDWm−2). Model results suggest that controlled harvesting of macrophyte biomass may be carried out without affecting macrophyte real net production, through the reduction of light limitation under the plant canopy. © 2000 Elsevier Science B.V. All rights reserved.